HUBUNGAN KECENDERUNGAN DEPRESI DENGAN STATUS GIZI PADA LANSIA DI UPTD GRIYA WERDHA SURABAYA[Correlation of Depression Tendency and Nutritional Status of Elderly in UPTD Griya Werdha Surabaya] - Hasna Rosida Putri; Triska Susila Nindya (Universitas Airlangga, 2019)
Malnutrition is one of the causes of health problems in the elderly. Nutritional status of the elderly can be affected by many factors, such as food intake, comorbidities, drugs consumption, physical activity, and depression. Depression status has a relationship with the nutritional status of the elderly by influencing the intake of the elderly. The purpose of this study was analyze the correlation and the risk of depression tendency with elderly nutritional status at UPTD Griya Werdha Surabaya. This study was a case-control design. The number of respondents were 30 elderly consist of 15 elderly in each case and control groups. The case group was elderly who had MNA score <24 points, while the control group was elderly who had MNA score of ≥24 points. Depression were measured by Short Geriatric Depression Scale (GDS). Spearman correlation test was used to analyze the data. Most of the elderly do not experience depression (GDS<5). There was a correlation between depression with nutritional status of the elderly (p=0.007). Depression elderly were 9.75 times more likely to malnourished than nutritional status [OR=9.75, 95% CI =`1.63 (1.45-1.81)]. Nutritional status was correlated with the tendency of depression in the elderly. It is necessary to increase more activities at the UPTD Griya Werdha Surabaya to reduce the risk of depression among elderly.